Miami classification for probe-based confocal laser endomicroscopy - Michael B. Wallace; Gregory Y. Lauwers; Y. Chen; Evelien Dekker; Paul Fockens; Prateek Sharma; Alexander Meining (2011)
An essential element for any new advanced imaging technology is standardization of indications, terminology, categorization of images, and research priorities. In this review, we propose a state-of-the-art classification system for normal and pathological states in gastrointestinal disease using probe-based confocal laser endomicroscopy (pCLE). The Miami classification system is based on a consensus of pCLE users reached during a meeting held in Miami, Florida, in February 2009.